The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1029/2009je003504
|View full text |Cite
|
Sign up to set email alerts
|

Mars ultraviolet dayglow variability: SPICAM observations and comparison with airglow model

Abstract: [1] Dayglow ultraviolet emissions of the CO Cameron bands and the CO 2 + doublet in the Martian atmosphere have been observed with the Spectroscopy for Investigation of Characteristics of the Atmosphere of Mars on board the Mars Express spacecraft. A large amount of limb profiles has been obtained which makes it possible to analyze variability of the brightness as well as of the altitude of the emission peak. Focusing on one specific season (Ls = [90,180]°), we find that the average CO peak brightness is equal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 48 publications
7
44
0
Order By: Relevance
“…A comparison of the obtained spectra with previous analyses of the SPICAM data set (Cox et al, ; Leblanc et al, ) shows a fully similar spectral shape but slightly lower intensities in our analysis for the Cameron bands and a larger difference (around 30%) for the CO 2+ UV doublet (not shown). This is mainly due to the use of a different detector efficient area.…”
Section: Comparison With Spicam Observationssupporting
confidence: 83%
See 2 more Smart Citations
“…A comparison of the obtained spectra with previous analyses of the SPICAM data set (Cox et al, ; Leblanc et al, ) shows a fully similar spectral shape but slightly lower intensities in our analysis for the Cameron bands and a larger difference (around 30%) for the CO 2+ UV doublet (not shown). This is mainly due to the use of a different detector efficient area.…”
Section: Comparison With Spicam Observationssupporting
confidence: 83%
“…A similar plot, but for the CO 2+ UV doublet, is shown in Figure . No graph showing the SZA variability of this emission was included in Leblanc et al () and Cox et al (). We have nevertheless included UV doublet peak intensities for three ranges of SZA from Figure 8 of Leblanc et al (), shown as green points in Figure .…”
Section: Comparison With Spicam Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…An average altitude offset of 2.4 km was found by Cox et al (2010) in their study of the SPICAM observations of the two emissions. Since the altitude of the two emissions covary and because the two CO 2 + UVD sources are both directly related to the CO 2 density distribution, we mainly concentrate on the comparison between the observed and simulated CO 2 + UV doublet emission.…”
Section: 1029/2019ja026596mentioning
confidence: 88%
“…Therefore, the value reported by Avakyan et al [1998] is 2.4 10 −16 cm −2 at 80 eV, and the correction has been applied for all the energies. Such a correction was known to be too high to account for the observed Cameron bands at Mars [ Erdman and Zipf , 1983], and the newly reevaluated cross section was divided by 2 in Simon et al [2009], Cox et al [2010], and Jain and Bhardwaj [2011b]. The recent experimental and theoretical work by Gilijamse et al [2007] re‐analyzed the radiative lifetime of CO(a 3 Π), and found a value of 3.16 ms, which is 3 times less than the value of [ Johnson , 1972] used previously to correct the cross sections.…”
Section: The Emission Uncertainties Sourcesmentioning
confidence: 99%